Association of Hospital-Level Acute Resuscitation and Postresuscitation Survival With Overall Risk-Standardized Survival to Discharge for In-Hospital Cardiac Arrest - Girotra, Saket (JAMA Netw Open, 2020)
IMPORTANCE: Survival after in-hospital cardiac arrest depends on 2 distinct phases: responsiveness and quality of the hospital code team (ie, acute resuscitation phase) and intensive and specialty care expertise (ie, postresuscitation phase). Understanding the association of these 2 phases with overall survival has implications for design of in-hospital cardiac arrest quality measures. OBJECTIVE: To determine whether hospital-level rates of acute resuscitation survival and postresuscitation survival are associated with overall risk-standardized survival to discharge for in-hospital cardiac arrest. DESIGN, SETTINGS, AND PARTICIPANTS: This observational cohort study included 86 426 patients with in-hospital cardiac arrest from January 1, 2015, through December 31, 2018, recruited from 290 hospitals participating in the Get With The Guidelines–Resuscitation registry. EXPOSURES: Risk-adjusted rates of acute resuscitation survival, defined as return of spontaneous circulation for at least 20 minutes, and postresuscitation survival, defined as survival to discharge among patients achieving return of spontaneous circulation. MAIN OUTCOMES AND MEASURES: The primary outcome was overall risk-standardized survival rate (RSSR) for in-hospital cardiac arrest calculated using a previously validated model. The correlation between a hospital’s overall RSSR and risk-adjusted rates of acute resuscitation and postresuscitation survival were examined. RESULTS: Of 86 426 patients with in-hospital cardiac arrest, the median age was 67.0 years (interquartile range [IQR], 56.0-76.0 years); 50 665 (58.6%) were men, and 71 811 (83.1%) had an initial nonshockable cardiac arrest rhythm. The median RSSR was 25.1% (IQR, 21.9%-27.7%). The median risk-adjusted acute resuscitation survival was 72.4% (IQR, 67.9%-76.9%), and risk-adjusted postresuscitation survival was 34.0% (IQR, 31.5%-37.7%). Although a hospital’s RSSR was correlated with survival during both phases, the correlation with postresuscitation survival (ρ, 0.90; P < .001) was stronger compared with the correlation with acute resuscitation survival (ρ, 0.50; P < .001). Of note, there was no correlation between risk-adjusted acute resuscitation survival and postresuscitation survival (ρ, 0.09; P = .11). Compared with hospitals in the lowest RSSR quartile, hospitals in the highest RSSR quartile had higher rates of acute resuscitation survival (75.4% in quartile 4 vs 66.8% in quartile 1; P < .001) and postresuscitation survival (40.3% in quartile 4 vs 28.7% in quartile 1; P < .001), but the magnitude of difference was larger with postresuscitation survival. CONCLUSIONS AND RELEVANCE: The findings suggest that hospitals that excel in overall in-hospital cardiac arrest survival, in general, excel in either acute resuscitation or postresuscitation care but not both; efforts to strengthen postresuscitation care may offer additional opportunities to improve in-hospital cardiac arrest survival.